2015
DOI: 10.1371/journal.pone.0116659
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Toxicity to Microcystis aeruginosa PCC 7806 and Its Microcystin-Lacking Mutant

Abstract: The adverse effects of microcystin (MC) produced by cyanobacteria have drawn considerable attention from the public. Yet it remains unclear whether MC confers any benefits to the cyanobacteria themselves. One suggested function of MC is complexation, which may influence the bioaccumulation and toxicity of trace metals. To test this hypothesis, we examined Cd toxicity to wild-type Microcystis aeruginosa PCC 7806 (WT) and its MC-lacking mutant (MT) under nutrient-enriched (+NP), phosphorus-limited (-P), and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Cyanotoxins may therefore be produced in response to high trace metal concentrations as a means of detoxification [125]. Huang et al [126] observed the effects of toxic levels of cadmium on Microcystis aeruginosa and found no evidence that microcystin can affect metal toxicity by regulating metal accumulation or by directly assisting in the detoxification.…”
Section: Trace Metals and Cyanotoxinsmentioning
confidence: 99%
“…Cyanotoxins may therefore be produced in response to high trace metal concentrations as a means of detoxification [125]. Huang et al [126] observed the effects of toxic levels of cadmium on Microcystis aeruginosa and found no evidence that microcystin can affect metal toxicity by regulating metal accumulation or by directly assisting in the detoxification.…”
Section: Trace Metals and Cyanotoxinsmentioning
confidence: 99%
“…Among the tested concentrations, 0.4 mg L −1 Cd(II) exhibited the strongest inhibitory effects, with a 4-day IR of 74.752% and a 10-day IR of 99.992% ( Figure 2 ). It is documented that M. aeruginosa PCC 7806 was susceptible to trace metal toxicity [ 17 ], while a M. aeruginosa strain isolated in the Czech Republic had high tolerance to 5.0–10.0 mg L −1 Cd(II) [ 18 ]. Therefore, it is possible that different strains of M. aeruginosa have different sensitivities to Cd(II)-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Use of different strains of M. aeruginosa might lead to a longer adsorption process (10 min) [ 24 ]. In our experiment, there was also a slow adsorption process following the initial 5 min rapid adsorption, suggesting that Cd(II) was removed via interactions with functional groups on the cell surface [ 8 , 17 ].…”
Section: Resultsmentioning
confidence: 99%